Influence of systemic antibiotic therapy on the development and progression of induced apical periodontitis in Wistar rats - Duarte Faria, Flávio [UNESP]; Cantiga-Silva, Cristiane [UNESP]; Cardoso, Carolina de Barros Morais [UNESP]; da Silva Machado, Nathália Evelyn [UNESP]; de Oliveira, Pedro Henrique Chaves [UNESP]; Justo, Mariana Pagliusi [UNESP]; Goto, Juliana [UNESP]; de Castilho Jacinto, Rogério [UNESP]; Sivieri-Araújo, Gustavo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Springer Nature, 2024)
The aim of this study was to investigate the influence of systemic antibiotic therapy on the development and progression of induced apical periodontitis (AP) in Wistar rats. Fifty-six rats were submitted to pulp exposure of the lower left first molar for the induction of AP. On the same day, intraperitoneal antibiotic therapy was administered once a day, for 15 days, until euthanasia. The groups were formed according to the different treatments (n = 8): C—control; GEN—treated with gentamicin (10 mg/Kg); AC—treated with amoxicillin (100 mg/Kg); MZ—treated with metronidazole (40 mg/Kg); AMP—treated with ampicillin (100 mg/Kg); AMC group—treated with amoxicillin + clavulanic acid (100 mg/kg); CLI—treated with clindamycin (60 mg/kg). After euthanasia, the jaws were collected and processed for (1) histological and histometric analysis using hematoxylin and eosin staining, (2) analysis of collagen fibers using Picrosirius Red staining and (3) bacteriological analysis using Brown–Brenn staining. The data were analyzed statistically (p < 0.05). AP induction was confirmed in all groups. The AMC group had the lower intensity of inflammatory infiltrate (p = 0.028) and less periapical bone resorption compared to control (p = 0.006). Regarding collagen maturation, PSR staining revealed a predominance of mature collagen fibers in all groups. The AC and AMC groups had the lower amount of mature fibers and the highest amount of immature fibers, compared to all other groups (p < 0.001). All groups showed bacterial contamination; however, the AC and AMC groups showed a lower extent of bacterial contamination compared to the control (p < 0.001). It can be concluded that systemic antibiotic therapy influences the development and progression of induced AP.
Keywords: Antibiotics; Apical periodontitis; Bone resorption; Endodontics; Inflammation; Pulp necrosis